Association of variants in angiotensin-converting enzyme and endothelin-1 genes with phototherapy in cutaneous T-cell lymphoma - Vašku, Vladimir (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Background. The cutaneous T cell lymphoma (CTCL) is a disease characterised bycutaneous infiltrates of malignant, clonally expanded T cells. Because individual genetic determination of angiogenetic and antioxidant properties ofblood vessels could be partly responsible for phototherapy in CTCL patients,three polymorphisms in angiotensin converting enzyme and endothelin-1genes were determined. Methods. 77 patients with CTCL, diagnosed and treated at the First Dermatological Clinic of St. Ann's Faculty Hospital Brno (46 men and 31 women, median age 62, range 26-80 years) were compared to a control non-CTCL group of the similar age and gender distribution (n=203: 137 men and 66 women, median age 54, range 27-86 years) with negative family history of severe skin diseases and without signs of malignancy. Diagnosis of CTCL was verified according to the clinical picture and histologically. The genotype distributions and allelic frequencies between CTCL with phototherapy and those without phototherapy were compared. Results. Significant differenceswere found in genotype distributions of insertion/deletion (I/D) ACE polymorphism between CTCL patients treated with phototherapy and those treated without it. Heterozygote ID was more frequent in the group treated with phototherapy (25/13 vs. 12/27, OR=4.33, 95% confidential interval 1.67-11.24, P=0.02). The 4A4A variant of -3A/-4A EDN1 is more frequent in patients treated with phototherapy (8/30 vs.1/38, OR=10.13,95% confidential interval 1.20-85.55, P=0.01). The GA and AA genotypes of G8002A EDN1 polymorphism are more frequent in CTCL patients treated with phototherapy compared to those without it (15/23 vs. 7/32, OR=2.98, 95% confidential interval 1.05-8.48, P=0.03). Discussion. Some polymorphic variants in ACE and EDN1 genes (a heterozygote I/D ACE, a homozyqote -4A-4A in -3A /-4A EDN1 and qenotypes GA and GG in G8002A EDN1) seem to carry an advantage for phototherapy effectiven
Keywords: Aleli; Alleles; dermatologija; Endotelin-1; Endothelin-1; Fototerapija; Genetics; genetika; geni; Genotip; Genotype; Kožne novotvorbe; limfom; Limfom T-celični, kožni; Lymphoma, T-Cell, Cutaneous; Peptidil-dipeptidaza A; Peptidyl-Dipeptidase A; Phototherapy; Polimerazna, verižna reakcija; polimorfizem; Polimorfizem (genetika); Polymerase Chain Reaction; Polymorphism (Genetics); Skin Neoplasms; Therapy